Pigs in public health. Issue 3 (27th May 2017) - Svendsen, Mette N.
Abstract: Animals are rare topics in public health science texts and speech despite the fact that animal bodies and lives are woven into the health of human populations, and vice versa. Years of ethnographic and documentary research – following pigs and their humans in and out of biomedical research – made me mindful and watchful of the porous passages between animal and human bodies and environments that do not confine themselves to 'national health programs' directed towards a specific (human) population. These unrecognized species encounters and relationships, which exceed the conventional framework of public health, made me re-evaluate both what 'public' and what 'health' means in public health. In this commentary I provide a short personal account of that intellectual journey. I argue that entanglements between species make it urgent that public health scholars investigate the moral, socio-economic, material, and bacterial passages between humans and animals that constitute the various publics of public health and profoundly shape the health of human and animal populations in a globalized world.